2016
DOI: 10.1007/s13277-016-4994-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and histone acetylation regulate the expression of MGMT and chemosensitivity to temozolomide in malignant melanoma cell lines

Abstract: Malignant melanoma is an aggressive, highly lethal dermatological malignancy. Chemoresistance and rapid metastasis limit the curative effect of multimodal therapies like surgery or chemotherapy. The suicide enzyme O6-methylguanine-DNA methyltransferase (MGMT) removes adducts from the O6-position of guanine to repair DNA damage. High MGMT expression is associated with resistance to therapy in melanoma. However, it is unknown if MGMT is regulated by DNA methylation or histone acetylation in melanoma. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Gene silencing and loss of expression of MGMT, tumor suppressor gene, was reported in various types of cancers including breast cancer, colorectal cancer, nonsmall-cell lung cancer, melanoma, gliomas, and gastric cancer that is not related to gene mutations, deletions, rearrangements, or RNA instability. 37,38 Hypermethylation in specific region of promoter was suggested as one of the possible mechanisms for MGMT gene silencing in various cancers. 10,11 In the case of breast cancer, the earlier studies have estimated the frequency of MGMT promoter methylation between 22% and 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing and loss of expression of MGMT, tumor suppressor gene, was reported in various types of cancers including breast cancer, colorectal cancer, nonsmall-cell lung cancer, melanoma, gliomas, and gastric cancer that is not related to gene mutations, deletions, rearrangements, or RNA instability. 37,38 Hypermethylation in specific region of promoter was suggested as one of the possible mechanisms for MGMT gene silencing in various cancers. 10,11 In the case of breast cancer, the earlier studies have estimated the frequency of MGMT promoter methylation between 22% and 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of pituitary adenoma is not fully understood, numerous experimental and clinical observations indicate that DNA repair enzyme O 6 -methylguanine-DNA methyltransferase (MGMT) is implicated in the pathogenesis of various tumor types, including pituitary adenoma ( 2 , 3 ). MGMT is a ubiquitous highly expressed enzyme that removes alkylating lesions at the O 6 position of guanine to repair DNA damage ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of HDAC inhibitors and DNMT inhibitors increases chromatin accessibility to cisplatin and doxorubicin, thus potentiating the anticancer effect of these cytotoxic drugs [ 134 ]. In addition, the combination of the DNMT inhibitor 5-aza-2′-deoxycytidine and the HDAC inhibitor trichostatin A sensitizes melanoma cells to temozolomide [ 135 ]. A phase I clinical trial studying the combination of decitabine and panobinostat with temozolomide reported that this triple therapy is safe in resistant metastatic melanoma patients and that 75% of the patients enrolled in the trial had either stable disease or complete response [ 136 ].…”
Section: Epigenetic Modifiers As Therapeutic Adjuvants For Melanoma Patientsmentioning
confidence: 99%